Phytoconstituent Analysis and Antibacterial Activity of Nitella flagelliformis A Braun Collected from a Pond of Khamargachi of Hooghly District West Bengal India - Sankar Narayan Sinha, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Phytoconstituent Analysis and Antibacterial Activity of Nitella flagelliformis A Braun Collected from a Pond of Khamargachi of Hooghly District West Bengal India